PAY STATION-BASED SYSTEM AND METHOD FOR DOCUMENT PROCESSING (2007)
The subject application is directed to a pay station-based kiosk system and method for document processing. A document processing device receives a document processing request and calculates costs associated with the performance thereof. Transaction identification data is then received from an associated user and compared to common identifier data. When the transaction identification data and the common identifier data match, the device prompts the user to pay at a counter at the service provider location and then performs the requested operation. The details of the transaction are then communicated to the server for storage in a database thereon in association with service provider data.